Complex network model indicates a positive effect of inspiratory muscles pre-activation on performance parameters in a judo match - Cirino, C.; Gobatto, C. A.; Pinto, A. S.; Torres, R. S.; Hartz, C. S.; Azevedo, P. H. S. M.; Moreno, M. A.; Manchado-Gobatto, F. B. (Scientific Reports, 2021)
This study investigated the effects of inspiratory muscle pre-activation (IMPA) on the interactions among the technical-tactical, physical, physiological, and psychophysiological parameters in a simulated judo match, based on the centrality metrics by complex network model. Ten male athletes performed 4 experimental sessions. Firstly, anthropometric measurements, maximal inspiratory pressure (MIP) and global strenght of the inspiratory muscles were determined. In the following days, all athletes performed four-minute video-recorded judo matches, under three conditions: without IMPA (CON), after IMPA at 15% (IMPA15), and at 40% (IMPA40) of MIP using an exerciser device. Blood lactate, heart rate and rating of perceived exertion were monitored, and the technical-tactical parameters during the match were related to offensive actions and the time-motion. Based on the complex network, graphs were constructed for each scenario (CON, IMPA15, and IMPA40) to investigate the Degree and Pagerank centrality metrics. IMPA40 increased the connectivity of the physical and technical-tactical parameters in complex network and highlighted the combat frequency and average combat time in top-five ranked nodes. IMPA15 also favoured the interactions among the psychophysiological, physical, and physiological parameters. Our results suggest the positive effects of the IMPA, indicating this strategy to prepare the organism (IMPA15) and to improve performance (IMPA40) in judo match.